Constitutive behavior of as-cast magnesium alloy Mg–Al3–Zn1 in the semi-solid state - Hu, K.; Phillion, A.B.; Maijer, D.M.; Cockcroft, S.L. (Elsevier, 2009)
The first reported tensile semi-solid stress/strain data for as-cast magnesium alloy Mg-Al3-Zn1 are provided. The results show that the maximum tensile stress at the solidus temperature (460°C) was 13 MPa. Furthermore, this alloy has no ductility above 540°C, and cannot sustain tensile stresses above 560°C. Based on these tests, an equation relating the maximum tensile stress with temperature was derived. The microstructure of the tested specimens was also examined to link the tensile properties to fraction solid and microstructure.
Keywords: Semi-solid; Magnesium alloy; Tensile properties; Hot tearing; Direct chill casting